Study on the Universal Tapered Segmental Ring Assembly Simulation Algorithm and Deviation Assessment: A Case Study on Metro Line Tunnel - Guoping Zheng; Jurij Karlovsek (Advances in Civil Engineering)
Universal tapered segmental ring system has been adopted to assemble tangent and curve line elements into the shield tunnels through the relative rotation of the adjacent front and rear rings, which simplifies the formwork design, demonstrates strong universality, and is easy for quality assurance. To evaluate the position deviation caused by the taper value and propose the assembly scheme for the contractor, this article developed the universal tapered segmental ring assembly simulation technology. Firstly, the assembly procedure of the universal tapered segmental ring system both in normal case and in special case is introduced, including the interval tunnel of special rings and actual engineering that needs deviation correction. Secondly, relevant core algorithms are introduced in detail, including the coordinate position algorithm of horizontal and vertical curves and computer graphic algorithm of spatial point rotating around any axis. Finally, this article takes a background metro line tunnel as a case to validate the algorithm and illustrate the assessment methodology of universal tapered segmental ring assembly accuracy. The sections with maximum deviation are found as an alert ahead of the shield advancing. In conclusion, the algorithms and methodology proposed in this article illustrate the excellent suitability and robustness in shield tunnels adopting a universal tapered segmental ring system in the stage of both design and construction.